Taking a line for a dance: asemic explorations - Wray, Thomas William Gabriel (2023)
Writing is a technology that has shaped human thinking since its invention and then widespread dissemination in the print age. Communication is going through radical changes in a new age but writing is still central to our every day reality. This body of research explores how elements of writing can be used to create art thereby subverting, remolding and giving new space to a means of codifying human experience fundamental to the civilized mind. It seeks to increase the dimensions occupied by what has become known as asemic writing and create connections with other art-forms. This study has a practical basis but aims to place this practice within the context of contemporary art.